Red Emitting Cerium(III) and Versatile Luminescence Chromaticity of 1D-Coordination Polymers and Heterobimetallic Ln/AE Pyridylpyrazolate Complexes - Youssef, Heba; Becker, Jonathan; Sedykh, Alexander E.; Schäfer, Thomas; Taydakov, Ilya V.; Müller-Buschbaum, Klaus; Justus Liebig University Giessen (My University, 2022)
Ten homoleptic lanthanide containing 1D-coordination polymers, three heterobimetallic lanthanide/alkaline earth complexes as well as two alkaline earth complexes of the formula 1∞[Ln(2-PyPz)3], [Tb2AE(2-PyPz)8], and [AE(2-PyPz)2(2-PyPzH)2], Ln=La−Nd, Sm−Ho, AE=Ca, Sr, Ba were obtained by reactions of the lanthanide (Ln) and/or the alkaline earth metals (AE) with the ligand 3-(2-pyridyl)pyrazole. Organic melt based and/or solvothermal synthesis results in a redox reaction. The investigated compounds exhibit fair thermal stability up to 400 °C. The Ce3+ compound exhibits a bright and red 5d-based broad band emission with a maximum at around 640 nm under UV excitation marking an example of a strong reduction of the exited 5d states of Ce(III). The co-doping of the Gd-containing coordination polymers with Eu3+ and Tb3+ allows for a shift in the chromaticity from the ion specific 4 f-based emission colors close to white light emission and thus for a versatile tuning of the chromaticity. The co-doping of Eu3+ with Tb3+ and vice versa shows metal-to-metal energy transfer (MMET) between 4 f-levels of Tb3+ and Eu3+, which influences the tuning of the emission colour.
Keywords: ddc:540